155k views
3 votes
Given the functions f and g below, find f(g(-3)).

f(x) = -x^2- 6x + 3
g(x) = -x - 3
Provide your answer below:
f(g(-3))

Given the functions f and g below, find f(g(-3)). f(x) = -x^2- 6x + 3 g(x) = -x - 3 Provide-example-1
User Aspasia
by
5.7k points

1 Answer

3 votes

Answer:

f(g(-3)) = 3

Explanation:

f(g(-3)) means that you have to solve for g(-3) and then solve for f(x) with the solution from g(-3)

g(x) = -x - 3

g(-3) = -(-3) - 3

g(-3) = 3 - 3

g(-3) = 0

Plug this into f(x).

f(x) = -x² - 6x + 3

f(0) = -(0)² - 6(0) + 3

f(0) = 3

f(g(-3)) = 3

User Ajsie
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.